Prototipe Sistem Pemantauan Tegangan Drop pada Sel Baterai 110 Vdc berbasis Aplikasi Telegram - Asrul Asrul; A. Abd. Jabbar; Ashadi Amir (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
Batteries are electrochemical devices as a source of DC voltage that is quite reliable and has high stability, so that the 110 Vdc Battery has a very important role at the substation (GI) to operate the driving motors at the voltage breaker (PMT), disconecting switch (PMS), supply PLC and telecommunication equipment in the SCADA system, as well as protection relays. If the 110 Vdc battery does not work properly, it can result in a major interference with the GI. So to help optimize battery maintenance, it needs an indication tool so that the battery can last a long time and can prevent damage to the battery prematurely. In this study, a voltage drop monitoring and detection system will be designed on 110 Vdc battery cells. The data will be forwarded to the database via the NodeMCU device to be sent to the Telegram application on the smartphone. The test was carried out by compiling 80 battery cells with a voltage of 1.5 volts in series to produce a voltage of 110 Vdc. Test results of the accuracy level of voltage readings achieved an average accuracy of 99.58% with an average difference of 0.42% while the test results of sending voltage data for each group were successfully carried out with excellent response and were able to display data / information on voltage values and conditions in telegram applications.